Influence of edapho-climatic factors on the sporulation and colonization of arbuscular mycorrhizal fungi in two Amazonian native fruit species - Oliveira,Arlem Nascimento de (2010)
Arbuscular mycorrhizal fungi (AMF) colonization and spore numbers in the rhizosphere of two fruit species, Paullinia cupana Mart. and Theobroma grandiflorum Schum., growing in a terra firme ecosystem in Central Amazonia were studied from August 1998 to May 2000. Climatic and edaphic factors were also determined to investigate their influence on mycorrhizal variables. Soil pH, Al, Mn and effective cation exchange capacity exhibited seasonal variations during the investigation period. Temporal variations in mycorrhizal colonization levels and spore numbers occurred, indicating seasonality. Moreover, the patterns of mycorrhizal colonization levels and spore numbers for both host species were similar during the studied period. Mycorrhizal variables were related to climatic and edaphic factors, however, the intensity and type of influence of climatic and soil characteristics on AMF development tended to vary with the season and host plant species in Central Amazonia conditions.